Modulation of mTOR signaling as a strategy for the treatment of Pompe disease - Jeong‐A Lim; Lishu Li; Orian S Shirihai; Kyle M Trudeau; Rosa Puertollano; Nina Raben (EMBO Molecular Medicine)
Abstract Mechanistic target of rapamycin (mTOR) coordinates biosynthetic and catabolic processes in response to multiple extracellular and intracellular signals including growth factors and nutrients. This serine/threonine kinase has long been known as a critical regulator of muscle mass. The recent finding that the decision regarding its activation/inactivation takes place at the lysosome undeniably brings mTOR into the field of lysosomal storage diseases. In this study, we have examined the involvement of the mTOR pathway in the pathophysiology of a severe muscle wasting condition, Pompe disease, caused by excessive accumulation of lysosomal glycogen. Here, we report the dysregulation of mTOR signaling in the diseased muscle cells, and we focus on potential sites for therapeutic intervention. Reactivation of mTOR in the whole muscle of Pompe mice by TSC knockdown resulted in the reversal of atrophy and a striking removal of autophagic buildup. Of particular interest, we found that the aberrant mTOR signaling can be reversed by arginine. This finding can be translated into the clinic and may become a paradigm for targeted therapy in lysosomal, metabolic, and neuromuscular diseases.